Elemental sulfur reduction by a deep‐sea hydrothermal vent Campylobacterium Sulfurimonas sp. NW10. (10th October 2020) - Wang, Shasha; Jiang, Lijing; Hu, Qitao; Liu, Xuewen; Yang, Suping; Shao, Zongze
Summary: Sulfurimonas species (class Campylobacteria, phylum Campylobacterota) were globally distributed and especially predominant in deep‐sea hydrothermal environments. They were previously identified as chemolithoautotrophic sulfur‐oxidizing bacteria (SOB), whereas little is known about their potential in sulfur reduction. In this report, we found that the elemental sulfur reduction is quite common in different species of genus Sulfurimonas . To gain insights into the sulfur reduction mechanism, growth tests, morphology observation, as well as genomic and transcriptomic analyses were performed on a deep‐sea hydrothermal vent bacterium Sulfurimonas sp. NW10. Scanning electron micrographs and dialysis tubing tests confirmed that elemental sulfur reduction occurred without direct contact of cells with sulfur particles while direct access strongly promoted bacterial growth. Furthermore, we demonstrated that most species of Sulfurimonas probably employ both periplasmic and cytoplasmic polysulfide reductases, encoded by genes psrA 1 B 1 CDE and psrA 2 B 2, respectively, to accomplish cyclooctasulfur reduction. This is the first report showing two different sulfur reduction pathways coupled to different energy conservations could coexist in one sulfur‐reducing microorganism, and demonstrates that most bacteria of Sulfurimonas could employ both periplasmic and cytoplasmic polysulfide reductases to perform cyclooctasulfur reduction. The capability of sulfur reduction coupling with hydrogen oxidation may partially explain the prevalenceof Sulfurimonas in deep‐sea hydrothermal vent environments.